Effects of selected leisure activities on preventing loneliness among older Chinese - Teh, Jane Kimm Lii; Tey, Nai Peng (Elsevier, 2019)
This study examined three types of leisure activities (playing cards/mahjong, watching TV/listening to the radio, and participation in social activities) among the older segment of the Chinese population, and the effects of these activities in preventing the feelings of loneliness. Data came from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), conducted in 2005, 2008, and 2011. The males, those who were educated, the young-old (aged between 65 and 74 years), urban dwellers, and living in institutions were more likely to participate in all three activities frequently. Frequent or occasional participation in these three activities was negatively associated with feelings of loneliness. The longitudinal study from 2005 to 2011 showed that respondents who frequently played cards/mahjong at baseline were less likely to feel persistent loneliness at the end of the 2011 wave. Instead, frequently watching TV/listening to the radio in 2008 was associated with lower odds in feeling persistent loneliness at the end of 2011. Hence, active participation in playing cards/mahjong and TV/radio entertainment can be effective treatment intervention against persistent loneliness among older Chinese. For the Chinese, a leisure activity steeped in a nation's culture and heritage, such as playing mahjong, may be used as an intervention strategy to prevent and alleviate chronic loneliness among older adults. © 2019 The Authors